Does context matter? - Vedder, Stefanie (Central European Public Administration Review, 2023)
Purpose: Over the past decades, public administration scholars and practitioners around the world have experimented with various administrative reforms to design governance models suitable to fulfil the tasks of public administration. Amidst this ongoing debate, (at least) three different and competing governance models can be distinguished: New Public Management, New Public Governance, and the (Neo) Weberian model. Despite each of these models claiming universal legitimacy, specific administrative branches in different administrative systems operate in unique contexts and handle varying tasks. The article delves into the question of whether and to what extent different branches of public administration within the same administrative system adopt global public administration ideas in a similar fashion. Design/Methodology/Approach: The article employs a comparative design to analyse the adoption of global public administration concepts across different administrative branches. Given their shared rigid Weberian tradition but divergent tasks and context, the study uses the German financial and social administrations as examples. The findings are derived from a survey of local agencies. Findings: The study reveals a persistent influence of strong Weberian traditions on the structural and operational makeup of both branches, indicating a significant path dependency in governance understanding. The characteristics of New Public Management and New Public Governance are comparatively more prominent in social than in financial administration, which can be attributed to differences in tasks and relations, especially with political actors. Academic contribution to the field: In addition to supplementing existing detailed analyses of the (non-)success of specific public administration reforms, the study takes a comprehensive view of the long-term development of public administration structure and perception, spanning multiple reforms. While acknowledging the formative influence of administrative tradition on the entire public administration system, the focus is on the nuanced effects of administrative traditions on diverse organisations, encouraging future comparative research. Originality/Significance/Value: In addition to the contribution to the field, our comparative methodology and empirical study makeup show the advantages of concentrating on a minimal number of paradigms that can be delineated as clearly as possible, instead of operationalising public administration reforms with a multitude of (potentially country-specific) indicators. With this approach, we lay the groundwork for the extension of the comparative design to other countries and administrative systems.
Keywords: finančna uprava; javna uprava; lokalna uprava; lokalno upravljanje; primerjalna metodologija; socialna uprava; upravna kultura; upravni sistemi